(untitled) (Research, Society and Development, 2021)
The objectives of this research were to evaluate the effects of the substitution of soybean oil by palm oil in the diet of Nile tilapia (Oreochromis niloticus) post-larvae, to observe the performance and attractiveness of the feed, and to evaluate the fatty acid methyl esters profile of palm oil. Four hundred Nile tilapias were used after hatching (seven days old), distributed in 20 fiberglass tanks of 20 L each. The experiment was carried out in a completely randomized design with five treatments and four replicates. The treatments consisted of different levels of inclusion of palm oil, which were: 0.0, 1.5, 3.0, 4.5 and 6.0 %. The concentration of monounsaturated and saturated fatty acids in palm oil was measured, resulting in high amounts of palmitic, oleic and linoleic fatty acids. Significant differences were observed for the variables final weight, total length, weight gain, specific growth rate and condition factor. No significant differences were observed for palatability of the diets. It is concluded that the inclusion of 3% or more palm oil in substitution of soybean oil during the masculinization stage of tilapia larvae contributes to the improvement of productive parameters.